Predictors of Early and Late Infarct Growth in DEFUSE 3 - Tate, William J.; Polding, Laura C.; Christensen, Søren; Mlynash, Michael; Kemp, Stephanie; Heit, Jeremy J.; Marks, Michael P.; Albers, Gregory W.; Lansberg, Maarten G. (Frontiers in Neurology, 2021)
Introduction - The goal of this study is to explore the impact of reperfusion and collateral status on infarct growth in the early and late time windows. Materials and Methods - Seventy patients from the DEFUSE 3 trial (Endovascular Therapy Following Imaging Evaluation for Ischemic Stroke) with baseline, 24-hour, and late follow-up scans were evaluated. Scans were taken with DWI or CTP at time of enrollment (Baseline), with DWI or CT 24-hours after enrollment (24-hour), and with DWI or CT five days after enrollment (Late). Early infarct growth (between baseline and 24-hour scans) and late infarct growth (between 24-hour and late scans) was assessed for each patient. The impact of collateral and reperfusion status on infarct growth was assessed in univariate and multivariate regression. Results – The median early infarct growth was 30.3 mL (IQR 16.4 – 74.5) and the median late infarct growth was 6.7 mL (IQR -3.5 – 21.6) in the overall sample. Patients with poor collaterals showed greater early infarct growth (Median 58.5 mL; IQR 18.6 – 125.6) compared to patients with good collaterals (Median 28.4 mL; IQR 15.8 - 49.3, unadjusted p=0.04, adjusted p=0.06) but showed no difference in late infarct growth. In contrast, patients who reperfused showed no reduction in early infarct growth but showed reduced late infarct growth (Median 1.9 mL; IQR -6.1 – 8.5) compared to patients without reperfusion (Median 11.2 mL; IQR -1.1 – 27.2, unadjusted p<0.01, adjusted p=0.04). Discussion – In the DEFUSE 3 population, poor collaterals predict early infarct growth and absence of reperfusion predicts late infarct growth. These results highlight the need for timely reperfusion therapy, particularly in patients with poor collaterals and indicate that the 24-hour timepoint is too early to assess the full impact of reperfusion therapy on infarct growth. Clinical Trial Registration Information - URL: http://www.clinicaltrials.gov. Unique identifier: NCT02586415